Evaluation of quality of life in type 2 diabetes mellitus patients using quality of life instrument for indian diabetic patients: A cross-sectional study - Reeni John; Sanjivani Pise; Leena Chaudhari; Prasanna R Deshpande (Wolters Kluwer Medknow Publications, 2019)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease with major impact on the quality of life (QoL) in terms of various domains such as social, physical, and mental well-being. Aim: This study aimed to study the factors determining the QoL in T2DM patients. Materials and Methods: A prospective, observational study was conducted in a tertiary care hospital for 6 months. Patients of age ≥18 years and diagnosed with T2DM for ≥6 months (with and without comorbidities) were enrolled for the study. The sociodemographic and clinical characteristics were noted in the self-designed pro forma. The QoL was assessed by the Marathi-translated version of QoL Instrument for Indian Diabetes Patients questionnaire of 34 items and 8 domains. The reliability was validated by Cronbach's alpha. The differences were analyzed by Mann-Whitney U-test and Kruskal-Walis test. Results: Out of 153 T2DM patients, majority were elderly males with mean age of 61.23 ± 11.4 years, married (83%), lower-middle income (57%), urban (51.6%), primary education (46.4%), had diabetes for 5 years or less (42.5%), had positive family history of diabetes (32.6%), and were treated by intensive therapy mainly insulin (41.2%). Statistically significant (P < 0.05) association was found between different domains of QoL and family history, hypertension, body mass index, educational status, marital status, income status, treatment, and complications. The domains of diet satisfaction and general health with the least mean estimates of 7.70 ± 2.62 and 8.25 ± 3.08, respectively, were predominantly affected. Conclusion: QoL is an important parameter in diabetes treatment modality. Different factors affected QoL in diabetics in our study. Further studies are definitely needed for better data generation at national level.